2006
DOI: 10.1097/01.aog.0000239100.16166.5a
|View full text |Cite
|
Sign up to set email alerts
|

Controlled-Release Misoprostol Vaginal Insert in Parous Women for Labor Induction

Abstract: I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 4 publications
1
19
0
Order By: Relevance
“…These complications are dose related higher the dose; more is uterine stimulation but shorter is the induction delivery interval [6]. With 50 lg vaginal misoprostol incidence of uterine contractile abnormalities have been reported to be 4.9% [5], 9% [9], 12% [1] and 26.92% in our study Ewert etal [10] observed these complications incidence as 3, 6.25, 10% with 25,100 and 200 lg controlled release vaginal inserts of misoprostol. While with 50 and 100 lg oral misoprostol uterine hyperstimulation incidence of 0.8% [5], 6.4% [11], respectively are reported.…”
Section: Discussionsupporting
confidence: 54%
“…These complications are dose related higher the dose; more is uterine stimulation but shorter is the induction delivery interval [6]. With 50 lg vaginal misoprostol incidence of uterine contractile abnormalities have been reported to be 4.9% [5], 9% [9], 12% [1] and 26.92% in our study Ewert etal [10] observed these complications incidence as 3, 6.25, 10% with 25,100 and 200 lg controlled release vaginal inserts of misoprostol. While with 50 and 100 lg oral misoprostol uterine hyperstimulation incidence of 0.8% [5], 6.4% [11], respectively are reported.…”
Section: Discussionsupporting
confidence: 54%
“…Since permanent fetal and maternal monitoring is not possible in daily hospital routine and missing experience in monitoring during the application, a general recommendation by the manufacturer is necessary. Offering a vaginal insert with a reduced dosage, for example, a 150 μg Misoprostol releasing less than 7 μg per hour could be an adequate alternative to decrease uterine hyperstimulation and avoid potential cesarean section due to fetal heart rate changes . Since we already know that a 150 μg MVI is only a little less effective than a 200 μg MVI it is not only speed and reduction in resource utilization that matters regarding the women's experience of induction of labor .…”
Section: Discussionmentioning
confidence: 99%
“…3 Several previous studies have demonstrated the dose-response, efficacy, and safety of multiple doses of the misoprostol vaginal insert in nonpregnant women 4 and in pregnant women at term. [5][6][7] In this report, we describe the results of a phase II doseranging study of the MVI 100, MVI 150, and MVI 200 dose reservoirs in participants who required cervical ripening before the induction of labor.…”
mentioning
confidence: 99%